2000
DOI: 10.1016/s0005-2736(00)00206-6
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of the hinge domain for dimerization of Ca2+-ATPase large cytoplasmic portion expressed in bacteria

Abstract: The large cytoplasmic domain of rabbit sarcoplasmic reticulum Ca2+-ATPase was overexpressed in Escherichia coli as a 48 kDa fusion protein, designated p48, containing an N-terminal hexa-His tag. Purification conditions were optimized, thus conferring long-term stability to p48. Circular dichroism spectroscopy and the pattern of limited trypsinolysis confirmed the proper folding of the domain. p48 retained 0.5 +/- 0.1 mol of high affinity 2',3'-O-(2,4,6-trinitrophenyl)adenosine-5'-triphosphate (TNP-ATP) binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
1
10
0
1
Order By: Relevance
“…Dimerization is sometimes considered as an activation mechanism [27]. Homodimer formation of the Ca 2+ -ATPase involves the N-terminal ends and the large cytoplasmic loop [28,29]. In the yeast and plant H + -ATPases, the native enzyme exists as a homodimer of catalytic subunits [4,9,13,30].…”
Section: The Regulatory Domainmentioning
confidence: 99%
“…Dimerization is sometimes considered as an activation mechanism [27]. Homodimer formation of the Ca 2+ -ATPase involves the N-terminal ends and the large cytoplasmic loop [28,29]. In the yeast and plant H + -ATPases, the native enzyme exists as a homodimer of catalytic subunits [4,9,13,30].…”
Section: The Regulatory Domainmentioning
confidence: 99%
“…Thus, the titration of Ca 2ϩ -ATPase and Ca 2ϩ uptake activities with fluorescein isothiocyanate (16), radiation inactivation analysis of pump activity and integrity (17,18), freeze-fracture and deep-etching of sarcoplasmic reticular membranes (19,20), and analysis with photoaffinity spin-labeled derivative of ATP (21) all suggested that the functional unit of the Ca 2ϩ -ATPase is a dimer. Furthermore, an analysis of a purified 48-kDa SERCA1 fusion protein by small angle x-ray scattering suggested a requirement of the hinge domain (amino acids 670 -728) region for self-association of the large hydrophilic domain into a dimer (22). Thus, it is possible that the mutant pumps affect the WT pump by way of protein interaction.…”
Section: Protein Levels Of Serca2bmentioning
confidence: 99%
“…[31] suggested a monomer–dimer transition model of Ca 2+ ‐ATPase, in which the cytoplasmic domains clap like a castanet duet, and Carvalho‐Alves et al . [32] proposed dimerization of the cytoplasmic domain of Ca 2+ ‐ATPase. Abe et al .…”
Section: Discussionmentioning
confidence: 99%
“…This state may loosely associate with another E state at the cytoplasmic domain, as shown by Carvalho‐Alves et al . [32]. E2( i )P, which corresponds to K + ‐insensitive E 2 P, is drawn as a compact form.…”
Section: Discussionmentioning
confidence: 99%